Assertive style: The balancing point in the educational process - Ponce-Blazquez, Esther; Navarro-Martinez, Oscar; Peña-Acuña, Beatriz (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores how interpersonal communication styles relate to individual balance across mental, emotional, and physical dimensions. The purpose is to examine the connection between communicative capacity and personal equilibrium, emphasizing how children evolve by transforming imbalance into balance through interpersonal interaction. A mixed-methods approach was employed, combining systematic observation, questionnaires, and interviews conducted in both individual and group settings. The sample comprised 315 participants. The analysis focused on how communication styles (assertive, aggressive, passive, and impulsive) correlate with ways of thinking, feeling, and acting. Findings reveal that assertive communication is significantly associated with emotional balance, while mental and physical imbalances are more frequently linked to aggressive, impulsive, or passive styles. The study concludes that fostering assertive communication can support holistic development and personal well-being. From an educational standpoint, the integration of methodologies that promote expression and reflection is recommended to enhance meaningful learning. These practices not only strengthen individual growth but also contribute to group cohesion and a balanced social and educational environment.